Airborne Particulate Matter Monitoring Using UAVs for Smart Cities and Urban Areas - Mayuga, Gian Paolo (Archīum Ateneo, 2018)
In smart cities and urban areas, localized weather monitoring will be a readily available feature. Checking the air quality in small area urban motifs, specifically schools and universities situated near a national primary road and mid to high-rise condominiums with increasing sources of pollutants, e.g. particulate matter (PM), becomes a need for risk assessment. An aerial sensor system, consisting of an unmanned aerial vehicle (UAV) and a sensor payload, is designed and implemented. Measurements for PM concentration are taken at various elevations, and during heavy and light traffic conditions. Results show trends relating PM concentration with elevation and traffic conditions.